Maternal exposure to endocrine disruptors and placental transmission: a pilot study. (2nd November 2018) - Caserta, Donatella; Pegoraro, Samantha; Mallozzi, Maddalena; Di Benedetto, Luisa; Colicino, Elena; Lionetto, Luana; Simmaco, Maurizio
Abstract: Endocrine disruptors (EDs) are known to affect maternal and child health. The objective of our study was to identify the association between some of the most important endocrine-disruptive substances (perfluorooctane sulfonate [PFOS], perfluorooctanoic acid [PFOA], di2-ethylhexyl-phthalate [DEHP] and mono2-ethylhexyl-phthalate [MEHP]) and both pregnancy variability and birth outcomes. We measured the concentration of the EDs in maternal and cord blood samples of 29 mother–newborn pairs from the Pertini Hospital in Rome between March and June 2016. Each mother reported demographic, life style and diet information. We compared concentrations of the endocrine disruptors between mother and newborn, and among different molecules. We analyzed differences and trends of each ED substance according to the demography and diet information. PFOA levels in maternal blood showed a negative association with newborn weight. Concentration levels of PFOA in both maternal and cord blood of those with physiological progression of pregnancy were higher in than in those with pathological pregnancies. MEHP trend showed a positive association with maternal age. These results confirm the maternal-to-fetus transfer of EDs through the placenta and the impact that endocrine disruptors have on pregnancy and birth outcomes. 摘要: 众所周知, 内分泌干扰物(EDs)会影响母婴健康。我们的研究目的是确定一些最重要的内分泌干扰物质(全氟辛烷值磺酸盐[PFOS]、全氟辛酸[PFOA]、二乙基己基邻苯二甲酸酯[DEHP]和单2-乙基己基邻苯二甲酸酯[MEHP])与妊娠变异性和出生结局之间的联系。我们收集了2016年3月至6月期间罗马佩尔蒂尼医院29对母婴血液样本中EDs的浓度, 以及每位母亲的个人背景、生活方式和饮食信息。我们比较了母亲和新生儿之间分泌干扰物的浓度。我们根据人口统计学和饮食信息分析了每种ED物质的差异和趋势。母体血液中PFOA水平与新生儿体重呈负相关。有生理性进展的孕妇以及脐带血中的PFOA浓度均高于有病理性进展的孕妇。MEHP趋势与母亲年龄呈正相关。这些结果证实了EDs通过胎盘的母婴传播, 以及内分泌干扰物对妊娠和分娩结果的影响。